(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2021)
The term “MDV” refers to a class of technologies that uses magnetic levitation to propel vehicles with magnets. Today the world is encountering one of the most serious scarcity of fossil fuels. Due to the increasing gasoline price and pollution from the exhaust of IC engines, so there is a necessity of any kind of alternate. This brought us towards the technology of using Magnet as a substitute for driving the vehicle in this rapidly developing automobile field. This project aims at developing a highly cost-effective and eco-friendly Magnet. Driven Vehicle (MDV) which is reliable and economical in the current scenario. The Vehicle work on the principle of MAGLEV (Magnetic levitation).Through this principle we levitate the driven shaft of our vehicle. Once the driven shaft is lifted we provide the torque to the driven shaft with the help of battery (by induced EMF) through this the driven shaft starts to rotate & required RPM can be achieved by induced EMF.For successful levitation and control of all 6 axes (degrees of freedom; 3 translational and 3 rotational) a combination of permanent magnets and electromagnets or superconductors as well as attractive and repulsive fields can be used. The primary ones used in maglev trains are servo-stabilized electromagnetic suspension (EMS), electrodynamics suspension (EDS).If two magnets are mechanically constrained along a single axis, for example, and arranged to repel each other strongly, this will act to levitate one of the magnets above the other. Another geometry is where the magnets are attracted, but constrained from touching by a tensile member, such as a string or cable. If one moves a base made of a very good electrical conductor such as copper, aluminium or silver close to a magnet, an (eddy) current will be induced in the conductor that will oppose the changes in the field and create an opposite field that will repel the magnet (Lenz’s law). At a sufficiently high rate of movement, a suspended magnet will levitate on the metal, or vice versa with suspended metal.